ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY ON CUSTOMER SATISFACTION - Yuliarto, Rudi Triadi (E-Jurnal Manajemen, 2021)
The purpose of this study was to determine the effect of service quality on customer satisfaction at the Pontianak Class II Port Authority and Harbormaster Office. The population used in this study were 81 people (census). This study uses multiple linear regression analysis, with SPSS statistical software. Service quality variables, with the dimensions of physical evidence (tangibles),  and assurance, each have a positive and significant effect on customer satisfaction, then the reliability, responsiveness and empathy variables each show no significant influence on customer satisfaction. This research found that the guarantee variable has the greatest influence on customer satisfaction. Keywords : physical evidence (tangibles), reliability, responsiveness, assurance, and empathy, customer satisfaction.